Superfluidity: a flexible functional architecture for 5G networks. Issue 9 (27th July 2016) - Bianchi, Giuseppe; Biton, Erez; Blefari‐Melazzi, Nicola; Borges, Isabel; Chiaraviglio, Luca; de la Cruz Ramos, Pedro; Eardley, Philip; Fontes, Francisco; McGrath, Michael J.; Natarianni, Lionel; Niculescu, Dragos; Parada, Carlos; et al.
Abstract: We propose the innovative architecture of Superfluidity, a Horizon 2020 project, co‐funded by the European Union. Superfluidity targets 5G networks, by addressing key network operator challenges with a multi‐pronged approach, based on the concept of a flexible, highly adaptive, superfluid network. Superfluidity supports rapid service deployment and migration in a heterogeneous network environment, regardless of the underlying hardware. The overall proposal offers advanced capabilities in terms of service deployment and interoperability, while guaranteeing high‐performance levels end‐to‐end. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : We propose the innovative architecture of Superfluidity, a Horizon 2020 project based on the concept of a flexible, highly adaptive, superfluid network. Superfluidity supports rapid service deployment and migration in a heterogeneous network environment, regardless of the underlying hardware. The overall proposal offers advanced capabilities in terms of service deployment and interoperability while guaranteeing high‐performance levels end to end.